The Effect of Regional Micro Business Policy Implementation on the Effectiveness of Leather Processing Industry Development in Garut Regency - Nanang Suparman (Publica: Jurnal Pemikiran Administrasi Negara, 2022)
This research is motivated by the development of a small industry in the leather sector and has become an icon of Garut Regency. The implementation of regional micro-business policies in fostering the leather and food processing industry is influenced by several aspects that make it easier or more difficult. This study aims to identify and examine the effect of regional micro-business policy implementation on the effectiveness of the leather processing industry development in the Garut Regency. The method used in this research is explanatory research to explain the causal relationship and hypothesis testing. Data collection was carried out by census by collecting data from research respondents and then tested according to research hypotheses that had been formulated. The data analysis results show a significant influence, but the policy's success has not been smooth. Factors that hinder the discrepancy between policies and the problems at hand are different understandings of policy goals and objectives, inadequate resources in implementing organizations and target groups, implementation procedures, communication and coordination, environmental support, and underlying values.